Enhancing Numeracy Skills in Kindergarten Children with Learning Disabilities Through Traditional Congklak Games - Irwanti, Sri; Azizah, Nur (Papanda Publisher, 2025)
Children with learning disabilities face significant challenges in developing foundational numeracy skills, with approximately 20% of children experiencing mathematical learning difficulties that can persist throughout their educational journey. Traditional pedagogical approaches often fail to address the multidimensional academic, social, and emotional needs of these learners. This study investigated the effectiveness of traditional congklak games as a culturally responsive intervention for enhancing numeracy skills among kindergarten children with learning disabilities. A classroom action research design following the Kemmis and McTaggart model was implemented across two cycles at a kindergarten in East Kalimantan, Indonesia. Seventeen children aged 5-6 years participated, including five specifically identified with learning disabilities. The intervention utilized traditional congklak games as the primary educational medium, incorporating systematic observation, per-cycle assessments, and structured interviews. Data were analyzed using qualitative descriptive methods supported by quantitative presentations. The intervention achieved remarkable improvements in numeracy competence, with independent mathematical achievement increasing from 11.8% at baseline to 94% following two implementation cycles. All five children with learning disabilities demonstrated measurable progress, with four achieving independent numeracy skills. Student engagement scores improved from 50.2% to 95.5%, while teacher effectiveness increased from 65% to 85% across intervention cycles. The findings demonstrate that culturally grounded, play-based approaches can effectively address learning disabilities' complex challenges. The intervention's success supports constructivist and social learning theories while providing practical evidence for inclusive educational practices. Traditional congklak games offered concrete mathematical experiences that reduced cognitive load while maintaining high engagement through culturally meaningful gameplay, creating equitable learning opportunities for children with diverse educational needs.